Pseudomonas Otitidis and Bacillus Subtilis from Saline Soil of Pakistan Exhibiting a Potential for Calcium Precipitation - Naila Idrees; Iqra Liaqat; Aisha Waheed Qurashi (International Journal of Economic and Environmental Geology, 2018)
Biomineralization is an important phenomenon reported in microbes of different environments. Present study deals with the analysis of mineralization potential of two salt tolerant species named IQ (Pseudomonas otitidis) and NAY (Bacillus subtilis) isolated from rhizosphere soil. These strains have the ability to show precipitation in acetate supplemented culture medium incubated for 21 days and showed positive results for urease tests. Increase in microbial precipitation was recorded in both strains. However, strain NAY (Bacillus subtilis) showed more precipitation as compared to other IQ (Pseudomonas otitidis). It was also observed that this precipitation was associated with increase in pH of the medium from 7.0 to 8.0 that started to increase on 4th day of culture incubation and increased slightly till 15 days. The FTIR analysis of the calcite crystals showed visible peaks at 711-1400 cm-1 wavelength. The visible bubbling appeared in acid test assay further confirmed the calcite precipitation. The mineral precipitation in both species under salt stress is significant for soil consolidation as well as adjusting soil pH under acidic conditions.